MONITORING MILK ANALOGUES FOR USE IN DIETARY NUTRITION - Гребенюк, Максим; Корецька, Ірина (SWorldJournal, 2024)
Analyzing people's diets in various parts of our planet has shown that drinking milk is a top-rated and beneficial product. Cow's milk is an excellent source of protein, calcium, and essential nutritional elements such as vitamin B12 and iodine. It also c